A composite coated ternary positive electrode material and preparation method thereof

By forming an aluminum-cobalt fluorine-coated coating on the surface of the ternary positive electrode material matrix, the problem of surface instability of the ternary positive electrode material during high-temperature cycle is solved, and the circulation capacity retention rate and electricity of the material are significantly improved. Chemical properties.

CN115458719BActive Publication Date: 2025-02-25HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211131793.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-02-25
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The surface lithium cobalt oxide layered ternary cathode material is unstable during the high-temperature cycle, resulting in serious attenuation of circulation capacity.

Method used

Using a composite coated ternary positive electrode material, an aluminum-cobalt fluorine-coated coating layer is formed on the surface of the ternary positive electrode material matrix, and a stable Al, Co, F co-censored coating layer is formed by synergistically using the fluorine source and the aluminum source.

Benefits of technology

The circulation capacity retention and electrochemical performance of the positive electrode material at high temperatures are significantly improved, oxygen precipitation is suppressed, and the stability and safety of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115458719B_ABST
    Figure CN115458719B_ABST
Patent Text Reader

Abstract

A composite coated ternary positive electrode material, the ternary positive electrode material comprises a ternary positive electrode material matrix and an aluminum cobalt fluorine coating layer wrapped on the surface of the matrix; the preparation method of the composite coated ternary positive electrode material comprises the following steps: (1) mixing a ternary precursor with a lithium source and a dopant M compound, sintering the mixture under an oxygen atmosphere at a sintering temperature of 850 to 950°C for 10 to 15 hours to obtain a ternary positive electrode material matrix; (2) mixing the ternary positive electrode material matrix with an aluminum source, a cobalt source and a fluorine source, sintering the mixture under an oxygen atmosphere to obtain the ternary positive electrode material. The present invention obtains HF by high-temperature decomposition of fluorine-containing organic matter, and utilizes the strong adsorption of HF by γ-alumina, and simultaneously composites cobalt-containing compounds to achieve Al, Co, and F co-coating, and the prepared positive electrode active high-temperature cycle capacity retention rate, high-temperature cycle impedance growth, and high-temperature storage performance are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a ternary positive electrode material and a preparation method thereof. Background Art

[0002] In recent years, electric vehicles have developed rapidly, and higher requirements have been placed on the energy density and cycle life of lithium-ion batteries. High-nickel layered oxide ternary positive electrode materials have attracted much attention due to their high energy density and relatively low manufacturing cost. However, with the increase of nickel content, there will be more unstable residual lithium compounds (Li2CO3 and LiOH) on the surface of high-nickel layered oxides, which will have a great impact on the material performance. At present, the problem of high residual lithium in high-nickel materials can be effectively solved by coating with Co-containing compounds, while also bringing higher energy density and conductivity. However, the surface-coated lithium cobalt oxide layer is difficult to exist stably for a long time during high-temperature cycling, and the surface impedance will increase sharply after a long cycle, resulting in serious attenuation of the cycle capacity. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a composite coated ternary positive electrode material and a preparation method thereof.

[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0005] A composite coated ternary positive electrode material comprises a ternary positive electrode material matrix and an aluminum-cobalt-fluorine coating layer wrapped on the surface of the matrix.

[0006] Furthermore, the chemical formula of the ternary cathode material matrix is ​​Li a Ni 1-x-y-z Co x Mn y M z O2, wherein 1<a≤1.1, 0<x≤0.1, 0<y<0.25, 1-xyz≥0.75, 0≤z≤0.02, and M is selected from one or more of Zr, La, Ce, Sr, W, Al, Mg or Y.

[0007] Furthermore, the chemical formula of the aluminum-cobalt-fluorine coating layer is Li b Co 1-m Al m O 2-n F n , where 0.5<b≤1.1, 0.002<m≤0.01, 0.005<n≤0.02.

[0008] Furthermore, the mass of the aluminum-cobalt-fluorine coating layer is 0.5wt% to 2wt% of the mass of the ternary positive electrode material matrix.

[0009] Under the same technical concept, the present invention also provides a method for preparing a composite coated ternary positive electrode material, comprising the following steps:

[0010] (1) mixing the ternary precursor with the lithium source and the dopant M compound, and sintering the mixture in an oxygen atmosphere at a temperature of 850 to 950° C. for 10 to 15 hours to obtain a ternary cathode material matrix;

[0011] (2) Mixing the ternary cathode material matrix with an aluminum source, a cobalt source and a fluorine source, and sintering them in an oxygen atmosphere to obtain the composite coated ternary cathode material.

[0012] Furthermore, in step (1), the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate.

[0013] Furthermore, the fluorine source in step (2) is one or more of vinyl fluoride, polyvinylidene fluoride, difluoromethane, trifluoroethane, 2-fluoroethanol or 2-fluoroacetic acid.

[0014] Furthermore, the cobalt source in step (2) is one or more of cobalt hydroxide, cobalt oxide, cobalt trioxide or cobalt oxyhydroxide.

[0015] Furthermore, the aluminum source in step (2) is γ-type alumina with a particle size of 1 to 100 nm.

[0016] Furthermore, in step (2), the mass of the aluminum source is 600-2000ppm of the mass of the ternary positive electrode material matrix, the mass of the cobalt source is 7000-21000ppm of the mass of the ternary positive electrode material matrix, and the mass of the fluorine source is 0.1wt%-0.6wt% of the mass of the ternary positive electrode material matrix.

[0017] Furthermore, the sintering in step (2) is a two-stage sintering, the first stage sintering temperature is 300-500°C, and the second stage sintering temperature is 600-800°C. The two-stage sintering temperature setting in step (2) can better play the synergistic effect of the fluorine source and the aluminum source. At 300-500°C, the preferred organic fluorine source is completely decomposed into HF, and at this temperature, γ-Al2O3 has a strong adsorption capacity for HF, allowing F to be better adsorbed on the surface of the material; then the second stage sintering is carried out at a higher temperature, allowing the F adsorbed on the surface to react with Al and Co at high temperature to form the aluminum-cobalt-fluorine co-coating layer. This temperature setting can greatly improve the utilization rate of the organic fluorine source, while allowing F to better combine with Co and Al, thereby improving the stability of the composite coating layer.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention obtains HF by high-temperature decomposition of fluorine-containing organic matter, and utilizes the strong adsorption effect of γ-alumina on HF, and at the same time composites cobalt-containing compounds to achieve Al, Co, and F co-coating, and the prepared positive electrode active high-temperature cycle capacity retention rate, high-temperature cycle impedance growth, and high-temperature storage performance are greatly improved.

[0020] (2) The aluminum-cobalt-fluorine coating layer in the present invention contains a relatively stable Co-F bond, and the bond length changes less during the cycle process, which is beneficial to the stability of the surface lattice oxygen, inhibits oxygen precipitation, and greatly improves the stability and safety of the material.

[0021] (3) The preparation method of the present invention is simple in process. At the same time, the introduction of the organic fluorine source can play a good role in promoting melting, which can significantly reduce the secondary sintering temperature and save energy. By selecting the aluminum source and the fluorine source, an aluminum-cobalt-fluorine composite coating layer with outstanding surface and interface stability is formed on the surface of the positive electrode material, which has a significant effect on improving the electrochemical performance of the positive electrode material at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is the FEI-SEM image of the composite coated ternary positive electrode material of Example 1.

[0024] Figure 2 This is the FEI-SEM image of the composite coated ternary positive electrode material of Example 2.

[0025] Figure 3 This is the FEI-SEM image of the composite coated ternary positive electrode material of Example 3.

[0026] Figure 4 This is the FEI-SEM image of the composite coated ternary positive electrode material of Example 4.

[0027] Figure 5 This is the FEI-SEM image of the composite coated ternary positive electrode material of Example 5.

[0028] Figure 6 This is the FEI-SEM image of the composite coated ternary positive electrode material of Comparative Example 1.

[0029] Figure 7 This is the FEI-SEM image of the composite coated ternary positive electrode material of Comparative Example 2.

[0030] Figure 8 This is the FEI-SEM image of the composite coated ternary positive electrode material of Comparative Example 3.

[0031] Fig. 9 It is a comparison chart of the storage DCR growth curves of the composite coated ternary positive electrode materials of Examples 1-5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0035] Embodiment 1:

[0036] A method for preparing a composite coated ternary positive electrode material comprises the following steps:

[0037] Step 1: Preparation of Li 1.06 Ni 0.776 Co 0.08 Mn 0.14 Zr 0.004 O2 ternary cathode material matrix

[0038] LiOH·H2O, Ni 0.8 Co 0.06 Mn 0.14 The (OH)2 ternary precursor and ZrO2 were mixed in a molar ratio of 1.06:1:0.004. The mixed raw materials were heated from room temperature to 500°C in an oxygen atmosphere at a heating rate of 3°C / min for 3 hours, then heated to 890°C for 12 hours, and naturally cooled to room temperature to obtain Li 1.06 Ni 0.776 Co 0.08 Mn 0.14 Zr 0.004 O2 ternary positive electrode material matrix.

[0039] Step 2: Preparation of composite coated ternary cathode materials

[0040] In Li 1.06 Ni 0.776 Co0.08 Mn 0.14 Zr 0.004 14000ppm Co(OH)2, 0.15wt% PVDF (polyvinylidene fluoride) powder and 600ppm γ-Al2O3 are added to the O2 ternary positive electrode material matrix, and after mixing evenly, two stages of sintering are carried out under an oxygen atmosphere. The first stage of sintering is sintering at 400°C for 3h, and the second stage of sintering is sintering at 675°C for 8h to obtain a composite coated ternary positive electrode material.

[0041] like Figure 1 As shown, the prepared composite coated ternary positive electrode material comprises a ternary positive electrode material matrix and a uniform aluminum-cobalt-fluorine coating layer wrapped on the surface of the matrix.

[0042] The prepared composite coated ternary cathode material was made into a soft pack battery with graphite as the negative electrode for electrochemical performance evaluation test. The charge and discharge test was carried out at 25°C, the voltage range was 2.8-4.25V, and the current density was 0.33C; the rate performance test was carried out at 25°C, the voltage range was 2.8-4.25V, and the current density was 3C; the high temperature cycle performance test was carried out at 45°C, the voltage range was 2.8-4.25V, and the current density was 1C; the storage performance test was carried out at 60°C, the voltage range was 2.8-4.3V, and the current density was 1C.

[0043] Embodiment 2:

[0044] Compared with Example 1, the only difference is that the amount of PVDF powder used in step 2 is 0.3 wt %.

[0045] Embodiment 3:

[0046] Compared with Example 1, the only difference is that the amount of PVDF powder used in step 2 is 0.45 wt%.

[0047] Embodiment 4:

[0048] Compared with Example 1, the only difference is that the second sintering temperature in step 2 is 650°C.

[0049] Embodiment 5:

[0050] Compared with Example 1, the only difference is that the second sintering temperature in step 2 is 700°C.

[0051] Comparative Example 1:

[0052] Compared with Example 1, the only difference is that the mixed material in step 2 does not contain PVDF powder.

[0053] Comparative Example 2:

[0054] Compared with Example 1, the only difference is that the fluorine source in step 2 is 900 ppm of LiF.

[0055] Comparative Example 3

[0056] Compared with Example 1, the only difference is that the aluminum source in step 2 is 600 ppm of α-Al2O3.

[0057] The composite coated ternary positive electrode materials obtained in Examples 1-5 and Comparative Examples 1-3 were subjected to electrochemical performance evaluation tests, and the test results are shown in Table 1 below:

[0058] Table 1

[0059]

[0060] Figure 1-8 FEI-SEM images of the ternary positive electrode materials of Examples 1-5 and Comparative Examples 1-3 show that after the introduction of the fluorine-containing coating layer, the surface coating marks of the examples are fewer, indicating that the introduction of fluorine has a melting effect, which can reduce the sintering temperature and save energy.

[0061] Fig. 9 The full-battery high-temperature storage DCR growth curve comparison diagram of the ternary positive electrode materials of Examples 1-5 and Comparative Examples 1-3 is shown. Combined with the test results in Table 1, it can be seen that: compared with the fluorine-free material in Comparative Example 1, the aluminum-cobalt-fluorine co-coating layer in Examples 1-5 can improve the high-temperature storage performance of the ternary positive electrode material; Inorganic fluorine source is used in Comparative Example 2, and the high-temperature long-term performance is improved, but compared with the material coated with organic fluorine source in Examples 1-5, the improvement in high-temperature cycle and storage performance is small; α-Al2O3 is used in Comparative Example 3, because of its weak adsorption effect on HF obtained by decomposition of organic fluorine source, fluorine cannot be well coated on the surface of the material to form a stable composite coating layer, and its high-temperature cycle and storage performance are significantly deteriorated compared with the examples. Figure 8 It can be seen that the surface coating marks have increased and the fluxing effect of fluorine has not been reflected.

[0062] In summary, it can be seen that aluminum, cobalt and fluorine co-coating on the material surface can improve high-temperature cycling and storage performance. At the same time, compared with the use of other aluminum sources and fluorine sources, the aluminum source and fluorine source used in the present invention have a synergistic effect, and the improvement of high-temperature cycling and storage performance is more obvious.

Claims

1. A method for preparing a composite coated ternary positive electrode material, characterized in that: The following steps are involved: (1) Mixing the ternary precursor with a lithium source and a dopant M compound, wherein the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate; sintering the mixture in an oxygen atmosphere at a temperature of 850 to 950° C. for 10 to 15 hours to obtain a ternary cathode material matrix; (2) Mixing the ternary cathode material matrix with an aluminum source, a cobalt source and a fluorine source, wherein the fluorine source is one or more of vinyl fluoride, polyvinylidene fluoride, difluoromethane, trifluoroethane, 2-fluoroethanol or 2-fluoroacetic acid; the aluminum source is γ-type alumina with a particle size of 1 to 100 nm; performing two-stage sintering in an oxygen atmosphere, wherein the first stage sintering temperature is 300 to 500°C and the second stage sintering temperature is 600 to 800°C, to obtain the composite coated ternary cathode material.

2. The preparation method according to claim 1, characterized in that: The cobalt source in step (2) is one or more of cobalt hydroxide, cobalt oxide, cobalt trioxide or cobalt oxyhydroxide.

3. The preparation method according to claim 1, characterized in that The mass of the aluminum source in step (2) is 600-2000 ppm of the mass of the ternary positive electrode material matrix, the mass of the cobalt source is 7000-21000 ppm of the mass of the ternary positive electrode material matrix, and the mass of the fluorine source is 0.1wt%-0.6wt% of the mass of the ternary positive electrode material matrix.

4. A ternary positive electrode material prepared by the method for preparing a composite coated ternary positive electrode material according to any one of claims 1 to 3, characterized in that: The ternary positive electrode material comprises a ternary positive electrode material matrix and an aluminum-cobalt-fluorine coating layer wrapped on the surface of the matrix.

5. The ternary cathode material according to claim 4, characterized in that: The chemical formula of the ternary cathode material matrix is ​​Li a Ni 1-x-y-z Co x Mn y M z O2, wherein 1<a≤1.1, 0<x≤0.1, 0<y<0.25, 1-xyz≥0.75, 0≤z≤0.02, and M is selected from one or more of Zr, La, Ce, Sr, W, Al, Mg or Y.

6. The ternary cathode material according to claim 4, characterized in that: The chemical formula of the aluminum-cobalt-fluorine coating layer is Li b Co 1-m Al m O 2-n F n , where 0.5<b≤1.1, 0.002<m≤0.01, 0.005<n≤0.

02.

7. The ternary cathode material according to claim 4, characterized in that: The mass of the aluminum-cobalt-fluorine coating layer is 0.5wt% to 2wt% of the mass of the ternary positive electrode material matrix.

Citation Information

Patent Citations

  • Core-shell type positive electrode material as well as preparation method and application thereof

    CN114975965A